Changing indications for liver transplant: slow decline of hepatitis viruses in Italy. Issue 8 (2nd August 2020) - Brancaccio, Giuseppina; Vitale, Alessandro; Signoriello, Giuseppe; Gaeta, Giovanni B.; Cillo, Umberto
Abstract: Background: The indications to LT are changing rapidly in Europe and the U.S. mainly due to the extensive use of direct-acting antiviral agents (DAA) against HCV. Italy was an endemic area for viral hepatitis. Methods: The study reviewed liver transplant registry of a leading Italian centre from the year 2014 (the year before the extensive use of DAA in Italy) to December 2018, with the scope of recording trends in indications. The indications were categorised as: HCV; HBV ± HDV; alcohol-dependent liver disease (ALD); NASH; mescellaneous. Transplants for decompensation or hepatocellular carcinoma were analysed separately. The data were analysed using standard statistical methods. Results: During the study period 463 LTs were accomplished. For the scope of the present study second transplants and transplant in patients <18 years were eliminated; in all, 397 patients were analysed. Overall, HCV infection was the main aetiological factor leading to transplant (139/397, 35%) followed by alcohol use (20.9%), HBV ± HDV (15.8%) and NASH (12.8%). In the decompensation group HCV decreased from 41.9% in 2014 to 14.3% in 2018 while alcohol increased ( p < .001); in the HCC group, HCV decreased from 52.6% to 34% and alcohol and NASH increased; the number and proportion of HBV infections remained stable over time, with a 56% prevalence of HDV among decompensated patients. Conclusion: LT landscape is rapidly evolving; hepatitis virus infections still maintain a remarkable proportion among the indications for LT in an area that reached in the past high endemic levels for hepatitis C and B.